Statin use and patterns of breast cancer recurrence in the Malmö Diet and Cancer Study. (February 2022) - Inasu, Maria; Feldt, Maria; Jernström, Helena; Borgquist, Signe; Harborg, Sixten
Abstract: Background: Accumulating evidence suggests that statins have a beneficial effect on breast cancer prognosis. Previous studies have reported a positive association between statin use and breast cancer survival; however, the relationship between statin use and patterns of breast cancer recurrence remains unclear. Patients and methods: We identified all Malmö Diet and Cancer Study (MDCS) participants diagnosed with incident invasive breast cancer between 2005 and 2014. The follow-up period began at breast cancer diagnosis and continued until the first invasive breast cancer recurrence event, death, emigration or the end of the follow-up (June 8, 2020). We estimated incidence rates (IRs) of recurrence and fit Cox regression models to compute crude and adjusted hazard ratios (HRs) with 95% confidence intervals (95% CIs) for disease recurrence to compare post-diagnosis statin users with non-users. Results: The final study cohort consisted of 360 eligible patients with a median follow-up of 8.6 years. Overall, there were 71 recurrences in 2932 total person-years. According to statin use, there were 14 recurrences in 595 person-years among statin users, and 57 recurrences in 2337 person-years in non-users. Statin use was associated with a reduced risk of breast cancer recurrence (HRadj  = 0.88 [95% CI: 0.82–0.96]). Regarding the pattern of recurrence, statin use was associated with a reduced risk of distant recurrence (HRadj  = 0.86 [95% CI: 0.80–0.94]) but not loco-regional recurrence (HRadj  = 0.97 [95% CI: 0.87–1.08]). Conclusion: In the MDCS, statin use was associated with a reduced risk of distant breast cancer recurrence, whereas no association between statin use and loco-regional breast cancer recurrence was found. This site-based difference in disease recurrence may be explained by statin's inhibition of epithelial-mesenchymal transition. Highlights: Breast cancer patients using statins have fewer recurrences. Post-diagnosis statin use specifically reduced the risk of distant recurrence. No protection against loco-regional recurrences was observed.